Neoadjuvant versus definitive chemoradiation for locally advanced esophageal squamous cell carcinoma - Post, Carl M.; Häfner, Matthias (Translational cancer research, 2017)
A standard treatment option for patients with locally advanced thoracic esophageal squamous cell carcinoma (TESCC) is trimodality therapy, often consisting of neoadjuvant concurrent chemoradiotherapy (CCRT) followed by surgery (1-4). However, transhiatal esophagectomy poses significant risks, including tracheal and pulmonary injury, anastomotic leak, vagus nerve injury, infection, and death. Therefore, two randomized trials have addressed this concern by comparing definitive CCRT (dCCRT) alone versus neoadjuvant CCRT (nCCRT) plus surgery in esophageal cancer (5,6). Both trials found no difference in overall survival (OS), but fewer local recurrences were observed in the nCCRT plus surgery groups. Major limitations of these trials included salvage therapy potentially confounding OS, the usage of induction chemotherapy (which is a widely utilized treatment strategy), patient selection based on induction chemotherapy response (6), and diminished applicability to current practice utilizing more advanced radiation techniques like intensity-modulated radiation therapy (IMRT). Consequently, recent high volume data addressing the therapeutic benefits of dCCRT versus nCCRT followed by surgery are lacking, and such data are needed to help inform the optimal management approach for TESCC.